Investigation of carrier dynamics of QDs using kinetic model and ultrafast spectroscopy - Jana, Bikash; Ghosh, Srijon; Dutta, Avisek; Baranov, Alexander V.; Fedorov, Anatoly V.; Patra, Amitava (Optical Materials: X, 2022)
The study of carrier dynamics of QDs is extremely important for developing efficient light-harvesting systems. Here, we investigate size-dependent hole transfer from CdSe QDs to 4-aminothiophenol (4-ATPh) ligand using ultrafast spectroscopy. The photoluminescence (PL) quenching is found to be 99% and 77% for 4-ATPh ligand capped 2.9 nm and 4.3 nm QDs, respectively. We propose a stochastic model for analyzing time-resolved fluorescence decay curves of QDs to estimate the average number of ligands around QDs and it is found that the larger number of ligands are attached with smaller QDs. The analysis of TA spectroscopy data reveals that the kinetics of hole transfer from 2.9 nm QDs to ligand is faster than 4.3 nm CdSe QDs, depending on the offset between valence band (VB) of the CdSe QD and the HOMO of 4-ATPh ligands, and the average number of 4-ATPh ligands attached to each CdSe QD. The fundamental study of ligand-induced charge transfer processes in QDs is important for QD-based solar cell applications.
CRIS-Team Scopus Importer:2022-01-07